REASON CAPITAL AND URBAN SPACE (DIMENSI: Journal of Architecture and Built Environment, 2005)
This work deals with the perception of urban space in the framework of globalisation and the withdrawal of the public sphere in the last decades of the XX century. The appearance of a new "market oriented reason" has changed dramatically the way public urban policy is discussed and carried out, with dramatic consequences to urban space. It is not only "form" that has changed, but also the whole perception of the role and the function of urban space. Urban space is the space of ideological constructions that hide its true identity. These ideological constructions are based on discourses full of "gaps". If these "gaps" were to be filled, the ideological discourse that sustains the commoditisation of space would crumble. Because of this commoditisation, public policies have shifted to a more pragmatic and market oriented course. In order to legitimise this process, a new discourse of public management has seen the day.